2010
DOI: 10.3109/13693780903096669
|View full text |Cite
|
Sign up to set email alerts
|

Spores ofMucor ramosissimus, Mucor plumbeusandMucor circinelloidesand their ability to activate human complement systemin vitro

Abstract: Complement activation by spores of Mucor ramosissimus, Mucor plumbeus and Mucor circinelloides was studied using absorbed human serum in the presence or absence of chelators (EGTA or EDTA). We found that the spore caused full complement activation when incubated with EGTA-Mg2+ or without chelators, indicating that the alternative pathway is mainly responsible for this response. In order to compare activation profiles from each species, ELISAs for C3 and C4 fragments, mannan binding lectin (MBL), C-reactive pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…However, Rhizopus species, which are responsible for almost 80% of infections, remain as the major cause of most mucormycosis cases. Also, a considerable number of mucormycosis cases have been associated with M. circinelloides [31]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Rhizopus species, which are responsible for almost 80% of infections, remain as the major cause of most mucormycosis cases. Also, a considerable number of mucormycosis cases have been associated with M. circinelloides [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Although M. plumbeus is extensively used for research purposes in biotransformation of natural products, no cases of mycosis have been so far linked to this species [31]. …”
Section: Discussionmentioning
confidence: 99%
“…There have been a few mucormycosis cases associated with M. ramosissimus . However, no mycosis cases associated with M. plumbeus have yet been reported ( 32 ). In this study, the genera of Mucor and Lichtheimia were represented in 29.17% and 10% of the 120 pure Mucorales cultures, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were incubated with absorbed serum in either GVB ++ , GVB-Mg-EGTA, or GVB-EDTA. After 60 min at 37°C, the samples were centrifuged at 1500 × g under refrigeration and the supernatants were collected and residual complement was measured in a spectrophotometer (Beckman Coulter, Brea, CA, USA) at 540 nm using the haemolytic system ( Granja et al 2010 ). Melanin and melanin ghost samples sensitised with guinea pig anti-melanin antibodies (1/200 dilution, previously titrated) were subjected to the same activation process but without the addition of chelators.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous fungi such as Aspergillus fumigatus , Candida albicans , C. neoformans , and Mucor spp activate the complement system, mainly by the alternative pathway ( Speth et al 2008 , Granja et al 2010 ). WĂŒnthrich et al (2015) demonstrated that dectin-2 (and to a lesser extent dectin-1)-mediated recognition of F. pedrosoi is largely responsible for the development of Ag-specific Th17 cells, while Mincle appears to inhibit the development of this T-helper subset.…”
mentioning
confidence: 99%